ROLE OF KAIZEN WORK CULTURE AS MODERATING WORK QUALITY AND PRODUCTIVITY IMPROVEMENT - Fransiskus Xaverius Candra Gunawan; Achmad Fauzi; Errick Worabay; Suryana Eka Dinisari Hafat; Yeremia Immanuel Nasution (Dinasti International Journal of Management Science, 2022)
Today, the role of a superior and strong work culture has become the main factor moderating performance improvement in a company. This can be seen in the quality and productivity of the work produced by the workers/employees and is a manifestation of the values ??formed by a habit and a strong desire to achieve the vision and mission. Kaizen's work culture has the principle of continuous and comprehensive improvement and prioritizes a high work ethic which has been widely adopted by many companies as a competitive advantage in facing change. This interest in Aini's work culture prompted us to conduct a literature review sourced from national, international journals and library research with the aim of studying the role of Kaizen Work Culture as Moderating Work Quality and Productivity Improvement. The results of the literature review found that a high work ethic and commitment to always adapt to the environment is a Kaizen strategy to face the dynamics of change based on the establishment of strong standard operating procedures, identifying problems in detail, conducting trials and continuous development, having a direct impact on improving work quality and productivity and becoming a competitive advantage for companies in the face of competition.